Ragam Bangunan Perundang-Undangan Hukum Keluarga di Negera-Negara Muslim Modern: Kajian Tipologis - Huda, Miftahul (Al-Manahij: Jurnal Kajian Hukum Islam, 2018)
The reality of the difference in applying Islamic law in the context of marriage law legislation in modern Muslim countries is undeniable. Tunisia and Turkey, for example, have practiced Islamic law of liberal nuance. Unlike the case with Saudi Arabia and the United Arab Emirates that still use the application of Islamic law as it is in their fiqh books. In between these two currents many countries are trying to apply the law in their own countries by trying to bridge the urgent new needs and local wisdom. This is widely embraced by modern Muslim countries in general. This paper reviews typologically the heterogeneousness of family law legislation of modern Muslim countries while responding to modernization issues. Typical buildings seen from modern family law reforms can be classified into four types. The first type is progressive, pluralistic and extradoctrinal reform, such as in Turkey and Tunisia. The second type is adaptive, unified and intradoctrinal reform, as in Indonesia, Malaysia, Morocco, Algeria and Pakistan. The third type is adaptive, unified and intradoctrinal reform, represented by Iraq. While the fourth type is progressive, unifiied and extradoctrinal reform, which can be represented by Somalia and Algeria.